2014
DOI: 10.3389/fgene.2014.00281
|View full text |Cite
|
Sign up to set email alerts
|

Persistent pharmacokinetic challenges to pediatric drug development

Abstract: The development of new therapeutic agents for the mitigation of pediatric disorders is largely hindered by the inability for investigators to assess pediatric pharmacokinetics (PK) in healthy patients due to substantial safety concerns. Pediatric patients are a clinical moving target for drug delivery due to changes in absorption, distribution, metabolism and excretion (ADME) and the potential for PK related toxicological (T) events to occur throughout development. These changes in ADMET can have profound effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…10 However, children vary in drug absorption, distribution, pharmacokinetics, immunologic response, and prevalence and type of comorbidities, all of which are likely to contribute to differences in the rates and variety of complications observed in pediatric patients. 11 Current literature supports that 19% to 51% of children experience adverse drug events (ADEs) and 27% to 41% experience venous access complications (VACs) while receiving OPAT. [12][13][14][15][16][17][18][19][20][21][22][23][24] Most studies, however, are limited in size, often exclude children with premorbid conditions, evaluate a single clinical diagnosis, and exclude patients treated with oral antibiotics.…”
mentioning
confidence: 99%
“…10 However, children vary in drug absorption, distribution, pharmacokinetics, immunologic response, and prevalence and type of comorbidities, all of which are likely to contribute to differences in the rates and variety of complications observed in pediatric patients. 11 Current literature supports that 19% to 51% of children experience adverse drug events (ADEs) and 27% to 41% experience venous access complications (VACs) while receiving OPAT. [12][13][14][15][16][17][18][19][20][21][22][23][24] Most studies, however, are limited in size, often exclude children with premorbid conditions, evaluate a single clinical diagnosis, and exclude patients treated with oral antibiotics.…”
mentioning
confidence: 99%
“…Developmental changes in drug disposition create the need for age‐appropriate pharmacotherapy . Although there have been many approaches for estimating pediatric drug dosing (e.g., extrapolation from adult data), these approaches are not adequate for many children, particularly for the very young patients (infants vs. children) . Developmental changes in drug response are difficult to predict at the individual patient level, in part due to our poor understanding of the mechanisms that regulate these developmental changes.…”
mentioning
confidence: 99%
“…In children of 1 year of age, the glomerular filtration rate (GFR) is nearly twice that of adults [16]. A higher dose per weight equation can compensate for this increase; however, as children age, additional adjustments are needed to accommodate for the gradual normalization to adult levels over time [15]. One study identified inadequate levels of efavirenz, an HIV drug, in 40% of children receiving weight-based doses recommended by the manufacturer [17].…”
Section: Pharmacokinetics In Childrenmentioning
confidence: 94%
“…Weight-based dosing in children assumes weight increases proportionally to age. Consequently, larger children are prone to overdose with this strategy unless maximum doses are predefined [15]. In children of 1 year of age, the glomerular filtration rate (GFR) is nearly twice that of adults [16].…”
Section: Pharmacokinetics In Childrenmentioning
confidence: 99%
See 1 more Smart Citation